Hybrydowe modele (formy) współpracy administracji publicznej z podmiotami prywatnymi – perspektywa prawna i praktyczna - Żywicka, Agnieszka; Bieś- Srokosz, Paulina (PRAWO i WIĘŹ, 2025)
This paper explores the phenomenon of hybrid forms of cooperation between public administration and private entities, which combine elements of public and private law. In light of increasingly complex public tasks and the demand for flexibility and efficiency in governance, traditional legal instruments are often insufficient. As a result, public authorities are increasingly using civil law tools — such as contracts, agreements, and informal arrangements — creating hybrid legal forms that transcend classical categorizations. The authors analyze selected models of such cooperation, including public-private partnerships (PPP), administrative settlements, and unnamed agreements, assessing both their legal basis and practical implications. Special attention is given to the challenges posed by such forms, including issues related to transparency, accountability, and legal certainty. The aim of the paper is to demonstrate the evolving nature of public administration’s legal toolkit and to argue for a more structured theoretical and legislative framework to address the growing role of hybrid legal forms in contemporary public governance.